KETERLIBATAN KELUARGA MUDA DALAM PROSES REGENERASI MAJELIS GEREJA DI GEREJA KRISTEN JAWA BAHTERA KASIH PEPANTHAN TEJOSARI - Daniel Imanuel Nugroho; Eliana Setyani (CENDEKIA: Jurnal Ilmu Pengetahuan, 2026)
ABSTRACT The participation of young families in church ministries is not always accompanied by readiness to assume leadership roles. At Gereja Kristen Jawa (GKJ) Bahtera Kasih, particularly in the Tejosari Pepanthan, young families actively engage in various non-structural ministries such as Sunday school, hospitality, singing ministry, and other church activities; however, they are reluctant to serve as church elders. This situation raises concerns regarding leadership regeneration, which may affect the sustainability of church governance and ministry. This study aims to analyze the forms of young families’ involvement and to identify the factors underlying their reluctance to enter church leadership positions. The research employed a qualitative case study approach using interviews, observations, and documentation. The research subjects included young families actively involved in church ministries as well as church administrators engaged in congregational development. Data were analyzed thematically to identify patterns of participants’ experiences and perceptions. The findings reveal that reluctance to serve as elders is influenced by low self-confidence, limited time due to work and family responsibilities, feelings of inferiority toward senior elders, and limited understanding of liturgy. These findings indicate that active ministry participation does not automatically translate into readiness for ecclesiastical leadership without adequate guidance. Therefore, churches need to develop structured mentoring and capacity-building programs for young families to support sustainable leadership regeneration. ABSTRAK Partisipasi keluarga muda dalam pelayanan gereja tidak selalu diikuti dengan kesiapan menerima peran kepemimpinan. Di Gereja Kristen Jawa (GKJ) Bahtera Kasih Pepanthan Tejosari, keluarga muda aktif dalam berbagai pelayanan non-struktural seperti sekolah minggu, konsumsi, singer, dan kegiatan gereja lainnya, namun belum bersedia menjadi majelis. Kondisi ini menimbulkan persoalan regenerasi kepemimpinan yang dapat memengaruhi keberlanjutan tata kelola pelayanan gereja. Penelitian ini bertujuan menganalisis bentuk keterlibatan keluarga muda serta mengidentifikasi faktor yang mendasari keengganan mereka memasuki jabatan kemajelisan. Penelitian menggunakan pendekatan studi kasus kualitatif melalui wawancara, observasi, dan dokumentasi. Subjek penelitian melibatkan keluarga muda yang aktif dalam pelayanan serta pengurus gereja yang terlibat dalam pembinaan jemaat. Data dianalisis secara tematik untuk menemukan pola pengalaman dan persepsi partisipan. Hasil penelitian menunjukkan bahwa keengganan menjadi majelis dipengaruhi oleh rendahnya rasa percaya diri, keterbatasan waktu akibat tuntutan pekerjaan dan keluarga, rasa minder terhadap majelis senior, serta keterbatasan pemahaman liturgi. Temuan ini menegaskan bahwa keterlibatan pelayanan belum otomatis menghasilkan kesiapan kepemimpinan gerejawi tanpa pembinaan yang memadai. Implikasinya, gereja perlu mengembangkan pendampingan terstruktur dan program penguatan kapasitas bagi keluarga muda guna mendukung regenerasi kepemimpinan yang berkelanjutan.